Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1089/jwh.2014.4907
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multimorbidity on Quality of Life Among Midlife Women: Findings from a U.S. Nationally Representative Survey

Abstract: Background: Little is known about the prevalence and cumulative burden of coexisting health conditions including chronic joint and muscular pain, urinary incontinence (UI), depression, osteoporosis risk, moderate/ severe vasomotor symptoms, and vulvar/vaginal atrophy (VVA). We surveyed a nationally representative U.S. sample of midlife (age 40-64 years) women to ascertain the prevalence, general health-related quality of life (HRQoL), and health-seeking behaviors associated with these six conditions. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
(36 reference statements)
1
29
0
2
Order By: Relevance
“…Participants were queried as part of an ongoing omnibus survey, through both landline and mobile telephone modalities. Results from the omnibus survey have been used in previous peer‐reviewed biomedical investigations …”
Section: Methodsmentioning
confidence: 99%
“…Participants were queried as part of an ongoing omnibus survey, through both landline and mobile telephone modalities. Results from the omnibus survey have been used in previous peer‐reviewed biomedical investigations …”
Section: Methodsmentioning
confidence: 99%
“…Age-related urinary changes, such as urinary incontinence, often lead to severe psychosocial problems that have a negative effect on the quality of life of women8, 9, 16 ) . This study found that the perimenopausal period exerted a greater impact on quality of life in relation to urinary losses.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the perimenopausal period exerted a greater impact on quality of life in relation to urinary losses. Several studies have demonstrated that UI has a negative influence on the quality of life of women aged between 40 and 65 years, as determined by the ICIQ-SF8, 9, 24 ) . In other words, regardless of the type of urinary loss, quality of life is compromised to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple long term conditions are associated with a wide range of adverse outcomes for individuals and the health system. These included: increased health service use (14,56,79,(89)(90)(91)(92), polypharmacy (56,90,(93)(94)(95)(96), hospital admissions (14,79,89,90,97,98), out-of-pocket expenses (99-103), and psychological distress (79,93,(104)(105)(106), along with reductions in physical functioning (79,(107)(108)(109)(110)(111)(112), quality-of-life (14,79,(113)(114)(115)(116)(117), employability (118)(119)(120),and continuity of care (56,93,121,122).…”
Section: Prevalence and Impactmentioning
confidence: 99%